2021
DOI: 10.1007/s10854-021-06122-y
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, illumination dependent electrical and photovoltaic properties of Au/BOD-Pyr/n-Si/In schottky diode

Abstract: 4,4-Difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY)-based BOD-Pyr compound was synthesized according to the literature and HOMO and LUMO energies of the BOD-Pyr were calculated by DFT/B3LYP/6-311G(d,p) method using on Gaussian 09W. Au/BOD-Pyr/n-Si/In Schottky diode were fabricated using thermal evaporation and spin coating technique. The electronic and photovoltaic properties of Au/BOD-Pyr/n-Si/In photodiode have been investigated by current-voltage (I-V) measurements at dark and under various illumination int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…• m ≈ 2 → IV. Region (I ∝ V ∼2 ): Trap-free SCLC conduction (all traps are filled), Childs Law (I ∝ V 2 ), and this region is also called as super ohmic or super linear conduction, and SCLC is assisted here by a single trap distribution at a single energy level lying below the valance band edge [71,80] (lying above the valance band edge in the case of using a p-Si wafer).…”
Section: Characteristics Of Cualv/n-si/al Nems Photodiodementioning
confidence: 99%
“…• m ≈ 2 → IV. Region (I ∝ V ∼2 ): Trap-free SCLC conduction (all traps are filled), Childs Law (I ∝ V 2 ), and this region is also called as super ohmic or super linear conduction, and SCLC is assisted here by a single trap distribution at a single energy level lying below the valance band edge [71,80] (lying above the valance band edge in the case of using a p-Si wafer).…”
Section: Characteristics Of Cualv/n-si/al Nems Photodiodementioning
confidence: 99%
“…Many attempts can be found in the literature to improve SBDs' electrical properties in different electrical applications by using organic semiconductors. As an example, Ongun et al [9] produced an Au/BOD-Pyr/n-Si/In rectification device and showed that the organic matter of BOD-Pyr has suitable semiconductor features for optoelectronic applications. In another study, Tan et al [10] conducted a comparative investigation on the effects of organic Metal Polymer Semiconductor (MPS) and inorganic Metal Insulator Semiconductor (MIS) interlayers in Au/n-GaAs Schottky diodes and they observed that MIS structure exhibits better performance although MPS exhibits rectifying properties.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the properties of organic materials, which are easy and low-cost production steps, can be used in electronic and optoelectronic fields, making it possible to produce heterojunction layer photosensitive devices. 8,[12][13][14][15][16][17] These organic layered heterojunction structures can be used instead of many inorganic-based materials in various optoelectronic applications such as photodiodes and solar cells. [18][19][20][21] Triphenylamine (TPA) derivatives as a hole transfer materials have become an exciting area in the last decades for their use in the fabrication of electroluminescent devices in different areas.…”
mentioning
confidence: 99%